Energy consumption in relation to the number of stacked packages in forced air pre‐cooling of apples. (14th March 2022) - Jia, Binguang; Yang, Luopeng; Zhang, Linhua; Li, Xiuling; Liu, Bing; Chen, Feiyong; Zhang, Qiangwu
Abstract: To better investigate the effect of the number of stacked packages on the seven‐eights cooling time and the specific fan energy consumption in forced air pre‐cooling (FAC), a three‐dimensional model of FAC in the stacked packages was developed. The predicted total pressure loss was less than the product of the number of stacked packages and the pressure loss of a single package. This was due to the pressure loss of the cold air flowing through the openings in the adjacent packages accounting for the dominant proportion of the stacked packages. The difference was used to prove the overestimation of the specific fan energy consumption calculated in terms of the product of the number of stacked packages and the pressure loss of a single package. In terms of the required parameters in the pre‐cooling industry, the optimal condition of three stacked packages at the air velocity of 1.0 m/s was suggested. Compared with the other complied conditions, the specific fan energy consumption of the optimal condition was reduced by more than 50% and 0.0289–0.975$ t −1, respectively. Practical applications: Forced air pre‐cooling was an effective way to retain freshness and to improve the economic benefit of horticultural products. The quantitative relationships among the number of stacked packages, the pressure loss, and the fan energy consumption were obtained by computational fluid dynamics (CFD) simulation. Based on the results, the optimal condition in forced air pre‐cooling of apples was suggested. Abstract : According to the difference in the pressure loss mechanism, the flow process of cold air through the openings in the stacked packages was classified into three modes. The total pressure loss was less than the product of the number of stacked packages and the pressure loss of a single package. The optimal condition of three stacked packages at the air velocity of 1.0 m/s was suggested.